The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
1992
DOI: 10.1111/j.1365-2249.1992.tb03044.x
|View full text |Cite
|
Sign up to set email alerts
|

Imbalance of CD4+ lymphocyte subsets in patients with mixed connective tissue disease

Abstract: SUMMARY CD4+ (helper/inducer) T lymphocyte subsets were studied in the peripheral blood from patients with mixed connective tissue disease (MCTD) by double‐labelling immunofluorescence. The proportion of CD4+CD45RA+ cells was higher (P < 0·01) when compared with controls, whereas CD4+CD29+ cells were markedly diminished (P < 0·001). CD4+CD29+ cells were lower than in patients with progressive systemic sclerosis who were studied in parallel. Upon stimulation with phytohaemagglutinin, CD4+ cells from MCTD patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1992
1992
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…In the early immune response, cross-talk between T cells and antigen-presenting cells initiate the production of certain patterns of cytokines, which was dictated by the type of invaded antigen, and orchestrates the subsequent development of CD4+T cell subsets [13]. Each subset plays a unique role in the elimination of invaded antigen, and dysregulated subset differentiation has long been associated with disease [29,30]. In the present study we demonstrated a Th17/Treg-related cytokine profile in patients with PBC with significant increases in IL-1b, IL-6 and IL-23, which were theoretically prone to Th17 differentiations and averse to Treg differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…In the early immune response, cross-talk between T cells and antigen-presenting cells initiate the production of certain patterns of cytokines, which was dictated by the type of invaded antigen, and orchestrates the subsequent development of CD4+T cell subsets [13]. Each subset plays a unique role in the elimination of invaded antigen, and dysregulated subset differentiation has long been associated with disease [29,30]. In the present study we demonstrated a Th17/Treg-related cytokine profile in patients with PBC with significant increases in IL-1b, IL-6 and IL-23, which were theoretically prone to Th17 differentiations and averse to Treg differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…8,11 But the recruitment of CD4 T lymphocytes cells into connective tissue might be responsible for the reduction of the number of these cells in peripheral blood. 16 Further studies are required to evaluate the role of these cells in graft survival.…”
Section: Discussionmentioning
confidence: 99%
“…Treg cells directly contact or secrete suppressive cytokines that suppress inflammation ( 26 , 27 ). Each subset plays a unique role, and the dysregulation of subset differentiation has been associated with disease ( 28 , 29 ). An imbalance between Th17/Treg cells has been reported in the progression of atherosclerosis ( 30 ).…”
Section: Discussionmentioning
confidence: 99%